THE INFLUENCE OF LEADERSHIP, MOTIVATION, AND WORKLOAD ON EMPLOYEE PERFORMANCE AT PUSDIKLAT BAHASA BADIKLAT, MINISTRY OF DEFENSE OF THE REPUBLIC OF INDONESIA - Sayyidinaa Zahra Ridha Pramitha; Yoyo Sudaryo; Andre Suryaningprang; Dadan Abdul Aziz; Mochammad Mukti Ali; Erna Herlinawati (Sean Institute, 2023)
The purpose of this study was to analyze the relationship between the influence of Leadership, Motivation, and Workload on Employee Performance at Pusdiklat Bahasa Badiklat, Ministry of Defense of The Republic Indonesia. In this study, the sample was employees at Pusdiklat Bahasa Badiklat, Ministry of Defense of The Republic Indonesia with a total sample of 30 people. This study uses quantitative methods with non-probability sampling technique (saturated sample), and data analysis tools using SPSS version 25.0 program. Based on the results of research at Pusdiklat Bahasa Badiklat, Ministry of Defense of The Republic Indonesia, shows that Leadership has a significant positive effect on Employee Performance, Motivation also has a significant positive effect on Employee Performance and Workload has a significant positive effect on Employee Performance, such as Leadership Style, Motivation and Workload Together.